A PORTRAIT OF SUNDANESE MAINTENANCE IN MULTILINGUAL LEARNING IN BOGOR - Krishandini Krishandini; Defina Defina; Endang Sri Wahyuni (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
Elementary pupils who used to be multilingual speakers began to change into monolingual. Giving Indonesian language as a language of unity to the elementary students does not mean hoping regional languages to become extinct, especially with the Sundanese language which is the top five in the number of speakers in Indonesia. Therefore, the researchers conducted research in several schools in Bogor with the aim of 1) knowing the level of institutional and government support in maintaining the use of Sundanese language in Bogor; 2) knowing the implementation of Sundanese language learning in Bogor; 3) knowing the process of multilingual learning. A quantitative method was used by distributing questionnaires to several primary schools in Bogor with a total of 47 teachers and doing observations of elementary students. Findings indicate that negative attitudes toward the Sundanese language are shown by elementary students with occasional use of Sundanese language in interacting with their friends. Institutions and governments are less supportive by not requiring each elementary to have a special Sundanese-speaking day school within a week and not allowing teachers to improve their abilities. The ability of Sundanese language teachers in elementary schools in Bogor is still low in scientific writing using Sundanese language.Keywords: Sundanese language, language maintenance, multilingual learningPOTRET PELESTARIAN BAHASA SUNDA DALAM PENBELAJARAN MULTI-BAHASA DI BOGORAbstrak Siswa sekolah dasar yang dulunya bermulti-bahasa sudah mulai berbahasa tunggal. Penetapan bahasa Indonesia sebagai bahasa persatuan tidak harus mematikan bahasa daerah, termasuk bahasa Sunda yang memiliki jumlah pembicara terbesar ke lima di Indonesia. Peneliti melakukan penelitian dengan tujuan 1) mengetahui tingkat dukungan lembaga dan pemerintah dalam pelestarian bahasa Sunda di Bogor; 2) mengetahui pelaksanaan pembelajaran bahasa Sunda di Bogor; 3) mengetahui proses pembelajaran multi-lingual. Penelitian menggunakan metode kuantitatif dengan membagikan angket ke beberapa sekolah dasar di Bogor dengan total 47 guru dan melakukan observasi terhadap siswa sekolah dasar. Temuan penelitian menunjukkan adanya sikap negatif terhadap bahasa Sunda pada siswa sekolah dasar dengan kadang-kadang menggunakan bahasa Sunda ketika berinteraksi dengan teman-temannya. Lembaga dan pemerintah kurang mendukung dengan tidak mewajibkan sekolah dasar untuk menggunakan bahasa Sunda sehari dalam seminggu dan tidak mengusahakan peningkatan guru dalam berbahasa Sunda. Keterampilan guru masih rendah dalam keterampilan menulis ilmiah dalam bahasa Sunda.Kata kunci: bahasa Sunda, pelestarian bahasa, pembelajaran multibahasa